Novel approach for pedestrian unusual activity detection in academic environment - Kamal Omprakash Hajari; Ujwalla Haridas Gawande; Yogesh Golhar (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
In this paper, we propose an efficient method for the detection of student unusual activity in the academic environment. The proposed method extracts motion features that accurately describe the motion characteristics of the pedestrian's movement, velocity, and direction, as well as their intercommunication within a frame. We also use these motion features to detect both global and local anomalous behaviors within the frame. The proposed approach is validated on a newly built proposed student behavior database and three additional publicly available benchmark datasets. When compared to state-of-the-art techniques, the experimental results reveal a considerable performance improvement in anomalous activity recognition. Finally, we summarize and discuss future research directions.